Parent coaching increases the parents' capacity for reflection and self-evaluation: results from a clinical trial in autism. Issue 3 (4th May 2018) - Siller, M.; Hotez, E.; Swanson, M.; Delavenne, A.; Hutman, T.; Sigman, M.
ABSTRACT: Family-centered parent coaching interventions in autism strive to encourage family engagement and support parent reflection and self-evaluation. This includes the parents' capacity to: (1) carefully observe the child's behavior; (2) reflect upon the child's thoughts, motives, and feelings; (3) consider links between the child's internal experiences and observable behavior; and (4) grapple with the complex interplay among the child's experiences and behaviors, contextual factors, parenting strategies, as well as parental goals and emotions. The current study reports data from a clinical trial of Focused Playtime Intervention (FPI), a parent coaching intervention targeting responsive parental behaviors and child communication. Seventy children with autism between 2 and 6 years and their parents were randomly assigned to participate in FPI for 12 weeks or an active control intervention. The Insightfulness Assessment was administered and used (a) to classify parents' baseline capacity for reflection and self-evaluation as either established (i.e., positively insightful) or emerging, and (b) to capture longitudinal change in the parents' capacity between baseline, exit ( 5 months after baseline), and follow up ( 14 months after exit) using a dimensional composite subscale score. Results revealed a significant treatment effect of FPI on growth in the parents' capacity for reflection and self-evaluation, conditional on the parents' classification at baseline. That is, parents whose capacity for reflection and self-evaluation was classified as emerging at baseline ( n = 42) showed higher rates of growth when assigned to FPI, compared to the control condition. A similar treatment effect was not found for parents whose baseline capacity for reflection and self-evaluation was classified as established (i.e., positively insightful). This is the first study to show that a family-centered parent coaching intervention effectively increases the capacity for reflection and self-evaluation in parents of young children with autism. This capacity may enable parents to adapt and implement intervention strategies flexibly across contexts, daily routines, and interactions.